IMPLEMENTATION OF INFORMATION TECHNOLOGY IN EDUCATION MANAGEMENT: EFFECTIVENESS AND CHALLENGES IN THE DIGITAL ERA - Marliana Marliana (International Journal of Teaching and Learning, 2025)
The use of information technology in education has great potential to improve the quality of teaching and learning. However, there are various significant challenges that must be overcome to achieve this goal. This study identified six main challenges in implementing information technology in education: access and infrastructure gaps, unequal digital competencies, data security and privacy issues, implementation and maintenance costs, adaptation of curriculum and teaching methods, and resistance to change. Addressing these challenges requires special attention, including providing equitable access, intensive training, strong data security policies, adequate budget allocation, and systematic changes in curriculum and teaching methods. By implementing the right strategy and collaboration between stakeholders, information technology can play an optimal role in transforming education to be more adaptive, inclusive and effective.